Development of Pametra Synectics-Based E-Book to Improve Fourth Grade Students' Writing Skills - Amalia, Amalia; Panca Dewi Purwati (Universitas Cokroaminoto Palopo, 2026)
This study is motivated by the low writing skills in simple texts, particularly reconstruction texts, among fourth-grade elementary school students. These difficulties are caused by struggles in developing ideas coherently, limited vocabulary, lack of self-confidence, and teacher-centered teaching methods. This development research aims to design, validate, and assess the effectiveness of the